Obsessive-compulsive symptoms and its relation to emotional disturbances among dental students during COVID-19 pandemic - Badrul Sham, Nur Zahirah; Faisal, Ghasak Ghazi; Radeef Al-Ani, Ali Sabri (Penerbit Universiti Sultan Zainal Abidin, 2024)
This study aimed to assess the rate of obsessive-compulsive symptoms and their relation to anxiety and depressive symptoms among dental students during the COVID-19 pandemic. A total of 138 Dental students were recruited in this cross-sectional study via an online self-rated questionnaires which were Obsessive-Compulsive Inventory-Revised (OCI-R), General Anxiety Disorder Scale-7 (GAD-7) and Patient Health Questionnaire (PHQ-9) to assess the obsessive-compulsive symptoms, anxiety and depression namely respectively. A rate of 56.5% of students were at high risk of obsessive-compulsive disorder (OCD). Obsessive-compulsive symptoms were significantly associated with anxiety and depressive symptoms. There was no significant difference between genders and OCD symptoms, however, students in clinical years were at higher risk for OCD. OCD symptoms are prevalent among dental students during the COVID-19 pandemic and many dental students suspected of having OCD will have anxiety and depression.